SIMULATION AND INTELLECTUAL ANALYSIS OF AUDIO FREQUENCY TRACK CIRCUIT PARAMETERS (Transport systems and technologies, 2022)
To improve the method of increasing the noise immunity of a audio frequency track circuit, based on cutting out interference in the intervals between useful signal pulses, an analysis was made of fluctuations in the signal transit time in the transmission path of a audio frequency track circuit depending on its operation parameters: signal current frequency, rail line length, insulation resistance and ambient temperature. For this, a simulation model of the operation of a audio frequency track circle has been developed. Based on the simulation results, a relational database was created with the values of measurement characteristics. With the use of intellectual analysis methods it was determined that the main factor affecting the signal transit time in the transmission path of the audio frequency track circuit is the frequency of the signal current. The main dependences of the operation parameters of the audio frequency track circuit and the signal transit time are determined. The obtained results help to increase the noise immunity of the operation of audio frequency track circuits due to a more precise adjustment of the interference cut-off interval between the useful signal pulses.
Keywords: audio frequency track circuit, simulation model, database, intellectual analysis, noise immunity